Safety Profile of Pertuzumab With Trastuzumab and Docetaxel in Patients From Asia With Human Epidermal Growth Factor Receptor 2-Positive Metastatic Breast Cancer: Results From the Phase III Trial CLEOPATRA. (28th May 2014) - Swain, Sandra M.; Im, Young-Hyuck; Im, Seock-Ah; Chan, Valorie; Miles, David; Knott, Adam; Clark, Emma; Ross, Graham; Baselga, José
Abstract: Introduction: We report detailed safety analyses by geographic region from the phase III study CLEOPATRA with pertuzumab, trastuzumab, and docetaxel in patients with human epidermal growth factor receptor 2 (HER2)-positive first-line metastatic breast cancer. Patients and Methods: Patients received pertuzumab/placebo at 840 mg in cycle 1 and 420 mg in subsequent cycles, and trastuzumab at 8 mg/kg in cycle 1 and 6 mg/kg in subsequent cycles; docetaxel was initiated at 75 mg/m 2 . All study drugs were given intravenously, 3 times weekly. Results: Docetaxel dose reductions below 75 mg/m 2 were more common in patients from Asia (47.0%) than other regions (13.4%); docetaxel dose escalations to 100 mg/m 2 were less frequent in Asia (2.4%) than other regions (18.7%). Rates of edema (26.1% and 5.4% for Asia and other regions, respectively), myalgia (42.3%, 14.7%), nail disorder (39.9%, 15.1%), febrile neutropenia (18.6%, 7.1%), upper respiratory tract infection (25.7%, 10.2%), decreased appetite (47.0%, 19.1%), and rash (44.3%, 22.0%) were at least twice as high in Asia as in other regions. Adverse events did not result in a reduction in the median number of study treatment cycles administered in patients from Asia. Efficacy analyses per region showed hazard ratios similar to those of the whole intention-to-treat (ITT) population for progression-free survival (ITT: 0.63; Asia: 0.68; other regions: 0.61) and overall survival (ITT: 0.66; Asia: 0.64; other regions: 0.66). Conclusion: Despite a higher proportion of docetaxel dose reductions in patients from Asia, survival benefits were comparable between regions. The benefit-risk profile of pertuzumab, trastuzumab, and docetaxel supports this regimen as the first-line therapy for patients with HER2-positive metastatic breast cancer from all geographic regions. Abstract : The authors report detailed safety analyses by geographic region from the phase III study CLEOPATRA with pertuzumab, trastuzumab, and docetaxel in patients with human epidermal growth factor receptor 2 (HER2)-positive first-line metastatic breast cancer. Despite more docetaxel dose reductions in patients from Asia, survival benefits were comparable between regions. The benefit-risk profile supports this regimen as the first-line therapy for patients with HER2-positive metastatic breast cancer from all geographic regions.